Inhouse Training Penerapan Pembelajaran Mendalam Melalui Koding dan Kecerdasan Artifisial bagi Guru SMP Negeri 37 Semarang - Nizaruddin Nizaruddin; Fenny Roshayanti; Sutrisno Sutrisno; Muhtarom Muhtarom; Muhammad Syaipul Hayat (Perkumpulan Kualitama Edukatika Indonesia, 2026)
The development of information technology demands a transformation of the education system to produce graduates who are adaptive to the digital era. This article aims to document and analyze the effectiveness of the Inhouse Training (IHT) program in improving the competency of teachers at SMP Negeri 37 Semarang in implementing coding and Artificial Intelligence (AI)-based deep learning. Using a participatory collaborative method with a needs-based approach, this program includes stages of socialization, offline training, implementation of Appropriate Technology (TTG), and intensive mentoring for three months. The results of the community service show a significant increase in teacher professional capacity, with a material usefulness score reaching 3.84 (96%) and participant satisfaction of 3.8 (95%). This intervention successfully transformed the teacher paradigm from limited digital literacy to the ability to develop contextual and innovative deep learning-based learning tools.